Combination of GLP-1 Receptor Activation and Glucagon Blockage Promotes Pancreatic β-Cell Regeneration In Situ in Type 1 Diabetic Mice - Liangbiao Gu; Dandan Wang; Xiaona Cui; Tianjiao Wei; Kun Yang; Jin Yang; Rui Wei; Tianpei Hong (Journal of Diabetes Research)
Pancreatic β-cell neogenesis in vivo holds great promise for cell replacement therapy in diabetic patients, and discovering the relevant clinical therapeutic strategies would push it forward to clinical application. Liraglutide, a widely used antidiabetic glucagon-like peptide-1 (GLP-1) analog, has displayed diverse β-cell-protective effects in type 2 diabetic animals. Glucagon receptor (GCGR) monoclonal antibody (mAb), a preclinical agent that blocks glucagon pathway, can promote the recovery of functional β-cell mass in type 1 diabetic mice. Here, we conducted a 4-week treatment of the two drugs alone or in combination in type 1 diabetic mice. Although liraglutide neither lowered the blood glucose level nor increased the plasma insulin level, the immunostaining showed that liraglutide expanded β-cell mass through self-replication, differentiation from precursor cells, and transdifferentiation from pancreatic α cells to β-cells. The pancreatic β-cell mass increased more significantly after GCGR mAb treatment, while the combination group did not further increase the pancreatic β-cell area. However, compared with the GCGR mAb group, the combined treatment reduced the plasma glucagon level and increased the proportion of β-cells/α-cells. Our study evaluated the effects of liraglutide, GCGR mAb monotherapy, and combined strategy in glucose control and islet β-cell regeneration and provided useful clues for the future clinical application in type 1 diabetes.